2016
DOI: 10.1007/s00402-016-2522-9
|View full text |Cite
|
Sign up to set email alerts
|

Plate augmentation and autologous bone grafting after intramedullary nailing for challenging femoral bone defects: a technical note

Abstract: The treatment of a large segmental defect of over 6 cm in a long bone is a challenging procedure. Treatment options include cancellous bone graft (e.g., the Masquelet technique), vascularized fibular graft (VFG), and internal bone transport (IBT) with an external fixator. These methods may be performed with intramedullary (IM) nailing or plate fixation to enhance stability or to lessen the time of external fixation. Each method has its own advantages and limitations. This study aimed to describe the advantages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The common causes of posttraumatic femoral nonunion with large segmental bone defect (> 6 cm) include acute bone loss, bone ischemia atrophy in nonunion sites, and surgical removal of dead bone and sclerotic bone after infection [ 1 , 2 ].Current treatment for the disease, in addition to the need of addressing the issue of bone nonunion with bone defect, soft tissue defect, nearby joint stiffness, deformities (rotation, angulation, and shortening), infection and many other issues should also be treated simultaneously [ 3 – 5 ]. At present, the common treatments include vascularized bone grafts (such as ribs, ilium, and fibula), intramembranous osteogenesis technique (Masquelet technique), and Ilizarov distraction osteogenesis [ 6 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The common causes of posttraumatic femoral nonunion with large segmental bone defect (> 6 cm) include acute bone loss, bone ischemia atrophy in nonunion sites, and surgical removal of dead bone and sclerotic bone after infection [ 1 , 2 ].Current treatment for the disease, in addition to the need of addressing the issue of bone nonunion with bone defect, soft tissue defect, nearby joint stiffness, deformities (rotation, angulation, and shortening), infection and many other issues should also be treated simultaneously [ 3 – 5 ]. At present, the common treatments include vascularized bone grafts (such as ribs, ilium, and fibula), intramembranous osteogenesis technique (Masquelet technique), and Ilizarov distraction osteogenesis [ 6 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Publications show that the healing rate for femoral shaft non-union is as high as 90% [ 14 18 ]. In our study, 29 patients (96%) finally achieved fracture healing, which is similar to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 29 patients (96%) finally achieved fracture healing, which is similar to previous reports. The fracture healing time with DP has been reported to be 5.2–6 months [ 14 16 ], which is dramatically shorter than that with EN/AP (6–13 months) [ 17 , 18 ] in previous reports. However, different results were observed in our study for the both healing time and the time to return to work, which were significantly shorter with EN/AP versus DP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue is that the intramedullary nail is unstable when xated in large segmental defects. Authors have reported to add another plate and bone grafting in dealing with nonunion after intramedullary nail xation [5]. We presumed that augmented plate could be useful when instability noticed during the second stage of this technique.…”
Section: Introductionmentioning
confidence: 95%